MULTIDIMENSIONAL SUSTAINABILITY ASSESSMENT OF RICE FARMING SYSTEMS INBALI: ATRIHITAKARANA-BASED APPROACH FORTRADITIONAL AGRICULTURAL DEVELOPMENT (Lex localis - Journal of Local Self-Government, 2025)
Tabanan Regency, Bali's primary rice-producing region, faces critical sustainability challenges including accelerated agricultural land conversion (2.92% annually) and demographic transitions with 70% of farmers exceeding 60 years of age. This study evaluates rice farming sustainability and develops evidence-based strategies grounded in the Tri Hita Karana (THK) philosophical framework. The research employed Multidimensional Scaling methodology through the Rapid Appraisal for Farm approach to assess sustainability across ecological, economic, social, technological, and institutional dimensions. Data were collected through structured interviews with 15 key informants and field observations in two subaks within the Yeh Empas irrigation system. Results indicate an overall sustainability index of 66.50% (moderately sustainable). Dimensional analysis revealed ecological (63.42%) and social (63.59%) as most vulnerable, while technological dimension achieved highest performance (71.42%). Leverage analysis identified five critical determinants: price stability (4.88), irrigation efficiency (4.53), intergenerational knowledge transfer (4.50),spatialplanningclarity(4.49),andawig-awigcontinuity(4.39).Monte Carlo validation confirmedmodelreliabilitywithdeviationsbelow2%. Five integrated strategies are proposed based on THK principles: institutional strengthening through spatial planning integration, youth engagement with traditional knowledge preservation, formal recognition of customary governance, market stabilization with digital cooperatives, and irrigation modernization with participatory management. This study contributes novel insights by demonstrating balanced sustainability in traditional systems, establishing economic centrality in multidimensional frameworks, and providing replicable methodology for integrating indigenous knowledge with scientific assessment.